La phrase emphatique et ses équivalents en slovene - Schlamberger Brezar, Mojca (Vestnik za tuje jezike, 2015)
On the basis of the grammar book Francoska slovnica po naše of Elza Jereb, we compare means of expression of emphasis in French and Slovene. The so-called emphatic clause in French represents a form of a sentence and we are looking for its equivalents in Slovene grammar. In French, we list the means under the labels of emphatic intonation, dislocation or extraction of a constituent, whereas in Slovene we speak of actualisation and emphatic particles. The means of extraction can be put in parallel with slovene where we can use demonstrative pronouns to point out on a part of a sentence. Within the dislocation, we can see that what is emphasized in French goes at the beginning of the sentence whereas in Slovene it is put to the end. Those differences should be taken into account as well in teaching of French as a foreign language as in translation.
Keywords: poudarjalna poved; francoščina; French; Slovene; slovenščina; ekstrakcije; dislokacije; translation; prevajanje; korpusna analiza